1974
DOI: 10.1126/science.186.4162.449
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Guanosine Monophosphate: Elevation in Degenerating Photoreceptor Cells of the C3H Mouse Retina

Abstract: As a result of an early deficiency in cyclic nucleotide phosphodiesterase activity, guanosine 3',5'-monophosphate accumulates in retinal photoreceptor cells before they begin to degenerate. It is suggested that degeneration of the photoreceptor cells is related to an imbalance in their metabolism or function which is caused by the elevated levels of cyclic guanosine monophosphate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
189
2
1

Year Published

1978
1978
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(200 citation statements)
references
References 14 publications
8
189
2
1
Order By: Relevance
“…Based on other phosphodiesterase mutants, mutation of the pde6c gene would be predicted to lead an accumulation of cyclic guanosine monophosphate (cGMP). 24 We observed a dramatic accumulation of cGMP in the pde6c w59 mutant retina at 4 d.p.f., demonstrating the biochemical consequence of pde6c gene mutation (compare Figures 3c and d) and also the absence of zpr1 cone photoreceptor staining in the mutant (Figure 3c). If cone cell death was mediated through a caspase-dependent mechanism, then we would expect to see activation of caspase-3.…”
Section: Resultsmentioning
confidence: 93%
“…Based on other phosphodiesterase mutants, mutation of the pde6c gene would be predicted to lead an accumulation of cyclic guanosine monophosphate (cGMP). 24 We observed a dramatic accumulation of cGMP in the pde6c w59 mutant retina at 4 d.p.f., demonstrating the biochemical consequence of pde6c gene mutation (compare Figures 3c and d) and also the absence of zpr1 cone photoreceptor staining in the mutant (Figure 3c). If cone cell death was mediated through a caspase-dependent mechanism, then we would expect to see activation of caspase-3.…”
Section: Resultsmentioning
confidence: 93%
“…(i) A deficiency in PDE catalytic activity and subsequent accumulation of cGMP (4). The truncation produced by the nonsense codon in exon 7 would occur within the region encoding the second putative cGMP noncatalytic binding domain, eliminating the membrane binding domain and the domain presumed to be essential for enzymatic function of cyclic nucleotide PDEs (26,36).…”
Section: Methodsmentioning
confidence: 99%
“…Mice homozygous for the mutation display a complete loss of rod photoreceptor cells by postnatal day 20 (2), yet cones survive much longer, and other retinal cells remain intact (3). The detection of high levels of cGMP, followed by photoreceptor degeneration, and absence of phosphodiesterase (PDE) activity suggested a defect in the enzyme itself (4). Using immunological methods it was shown that at least one of the two large subunits of PDE is present at low levels in the homozygous mutant mouse and that a normal subunit complex, a,8y2 (5,6), which is essential for regulation of cGMP levels in the phototransduction cascade, is not formed (7).…”
mentioning
confidence: 99%
“…PDE6 regulates rod cGMP levels, which in turn govern their cGMPgated cation channels (Cobbs and Pugh, 1985). The nonfunctional PDE6 therefore results in cGMP accumulation and subsequent abnormally high Ca 2ϩ levels in the rd1 photoreceptors (Farber and Lolley, 1974;Fox et al, 1999). By mostly unknown routes, this leads to an apoptotic-like rod cell death (Chang et al, 1993;Portera-Cailliau et al, 1994), followed by a mutationindependent cone death.…”
Section: Introductionmentioning
confidence: 99%